Engaging Community Members in Providing Support for the Dying and the Bereaved: Activities in Social Work Community Practice. Issue 4 (December 2018) - Crowe, Kelsey; D'Andrade, Amy
In this practice note, the authors describe three main community engagement strategies around empathy in times of suffering: (1) raising public awareness about the value of community support in times of grief with the creation of a neighborhood-based public campaign; (2) providing educational, skill-building workshops to instill confidence and communication skills among lay people in community, business, and medical settings that want to connect with people they know experiencing a personal difficulty; and (3) publishing a lighthearted, illustrated trade book and website/blog to make a difficult topic palatable and engaging to a broad audience. Activities were housed in a fiscally sponsored nonprofit the authors founded in 2014 called Help Each Other Out.